Fibromyalgia as a Predictor of Complex Regional Pain Syndrome After Distal Radius Fracture. (July 2019) - Lipman, Marc D.; Hess, Daniel E.; Werner, Brian C.; Deal, D. Nicole
Background: Complex regional pain syndrome (CRPS) can be a devastating complication following extremity injury, but risk factors are not well understood. The purpose of this study was to investigate the association between fibromyalgia and the development of CRPS after distal radius fracture.Methods: The PearlDiver Medicare database was queried using International Classification of Diseases, 9th Revision (ICD-9) and Current Procedural Terminology (CPT) codes for diagnoses and treatments of distal radius fractures. Patients were separated into fibromyalgia and control cohorts, and the prevalence of CRPS was measured at 3, 6, 9, and 12 months from the date of injury or procedure. Demographic factors, treatment modality, and comorbid conditions were analyzed by multivariable logistic regression to reduce confounding and identify additional risk factors.Results: Database queries yielded 853 186 patients diagnosed or treated for distal radius fracture, with 6% having previous diagnosis of fibromyalgia. The prevalence of CRPS following distal radius fracture was increased at 3, 6, 9, and 12 months in the fibromyalgia cohort compared with the control c, with a 1-year incidence of 0.51% compared with 0.20% (odds ratio [OR], 2.54, P < .001). Multivariable logistic regression supported the association, with estimated OR of 2.0 ( P < .001). In addition, female gender, surgical or manipulative treatment, and anxiety were positively associated with CRPS, and age >65, diabetes, and heart failure were negatively associated.Conclusions: While the basis of the association between fibromyalgia and CRPS is unknown, our data suggest that it could serve as a useful predictor of CRPS risk, promoting increased vigilance for CRPS symptoms and earlier recognition and treatment, thereby improving patient outcomes.